Estudo da fauna de Doryctinae (Hymenoptera: Braconidae) em áreas de cerrado no estado de São Paulo, Brasil - Pinto, Clóvis Sormus de Castro (Universidade Federal de São Carlos, 2010)
The Hymenoptera parasitoids are a key group in establishing priorities in programs aimed at conservation, given the high proportion of the diversity of insects. The parasitoids have great importance in maintenance of the environmental balance in population control of various species of hosts. This paper proposes a faunistic survey of the material deposited in the Coleção Taxonômica do Departamento de Ecologia e Biologia Evolutiva da Universidade Federal de São Carlos (DCBU). Samples were collected in 11 municipalities of São Paulo, each with a collection point, except the municipality of São Carlos with 6 points. For the capture of insects, were used: Malaise trap, water-pan trap, light trap and "sweeping" of the vegetation. We studied Doryctinae 2.031 individuals distributed in 36 genera described valid. The municipality of San Carlos had the highest number of Doryctinae obtained from 865 individuals and frequency of occurrence of 42.61%. Santa Rita do Passa Quatro was the location that showed the greatest wealth of genres, 22 in all, and also the largest number of genera exclusive to the location (4) in the study. Heterospilus Haliday was the dominant genus with almost 80% of the total specimens collected (1.603). Most Doryctinae studied were collected by sweeping the vegetation with 61% of the total Doryctinae collected by this technique (1.239). Although about half of the biome has been destroyed or turned into various types of land use, and rather fragmented, the Cerrado in São Paulo had become very abundant and rich in genus of the Doryctinae. Was described 3 new species and recorded 3 new genera for the Cerrado.
Keywords: Diversidade biológica; Hymenoptera; Braconidae; Doryctinae; CIENCIAS BIOLOGICAS::ECOLOGIA